Magnesium Sulphate as a Tocolytic Agent In Preventing Preterm Labour (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Preterm labor is an obstetric emergency. Magnesium Sulfate (MgSO4) is often used as a first-line therapy for that purpose as it is a highly effective tocolytic with fewer side effects than other tocolytics. This study aimed to evaluate effectiveness of MgSO4 as a tocolytic agent in preterm labor.  Materials and methods: A prospective comparative study was conducted in the Department of Obstetrics and Gynecology of CMCH, Chattogram, from June 2020 to November 2020. One hundred singleton pregnant women with preterm labor were included in this prospective comparative study. Patients were divided into two groups according to their cervical dilatation. Fifty patients who   as tocolytic (Group A) and for 50 patients who had cervical dilatation >4 cm, spontaneous vaginal delivery was allowed (Group B). Both groups were observed for at least 48 hours to see labor progression.   had cervical dilatation